The influence of interviewers on survey responses among female sex workers in Zambia - Harling, Guy; Bärnighausen, Till (BMC medical research methodology, 2019)
Interviewers can substantially affect self-reported data. This may be due to random variation in interviewers’ ability to put respondents at ease or in how they frame questions. It may also be due to systematic differences such as social distance between interviewer and respondent (e.g., by age, gender, ethnicity) or different perceptions of what interviewers consider socially desirable responses. Exploration of such variation is limited, especially in stigmatized populations.
Gesehen am 08.04.2019